(untitled) (Journal of Science and Technology, 2016)
In this paper, the authors examined the role of market women in the informal urban economy and the factors that threaten the effective performance of their roles. Interviewing 360 foodstuff sellers from the Kumasi Central Market and the Race Course Markets, the authors identified that the market women had made significant contributions towards Ghana’s fiscal decentralisation through the payment of levies and rents. They have also created jobs, provided incomes for households, ensured food security and sufficiency, and provided a platform for generational development of entrepreneurial skills and competence. However, their roles in the informal economy were constrained by the inadequate basic infrastructure in the markets, limited access to credit facilities and transportation difficulties. The paper therefore recommended the provision of basic life enhancing infrastructure and credit facilities complemented with capacity building in business management.